DNA/RNA hybrid profiling in autistic patients: A focus on mRNA and non-coding RNA variations - Leila Kianmehr; Kasra MokhtarZadeh; Zeynep Yilmaz; Hadi Darzi Ramandi; Ecmel Mehmetbeyoglu Duman; Elif Funda Sener; Serpil Taheri; Minoo Rassoulzadegan (PLoS ONE, 2025)
Autism spectrum disorder (ASD) is a set of genetically heterogenous neurodevelopmental disorders characterized by core symptoms including impaired social interaction, communication deficits, and restricted or stereotyped behaviors. While a significant number of cases are not explained by Mendelian inheritance, there is growing evidence for implication of non-coding RNAs (ncRNAs) in the development and inheritance of ASD. Transcriptional studies often face challenges due to patient-specific variations in gene expression and technical differences in preserving RNA integrity. We propose that isolating RNA from DNA/RNA hybrids provides a robust method to reliably capture transcriptional information. We performed a whole transcriptome analysis on blood samples from ASD patients and healthy controls to investigate transcripts associated with DNA/RNA hybrids. We identified 278,300 novel transcripts across 68,487 DNA/RNA hybrid loci, with significant enrichment in exonic and intronic regions. The novel long non-coding RNAs (lncRNAs) we found showed higher expression levels compared to known transcripts. Differential expression analysis revealed 301 significantly upregulated and 401 downregulated known transcripts in ASD samples compared to controls (|log 2 -fold change| > 1 and adjusted p-value < 0.05). Through qRT-PCR validation, we confirmed the significant upregulation of RN7SK and SMARCC2 associated with DNA/RNA hybrids in ASD patients. Pathway and enrichment analyses highlighted mitochondrial dysfunction and energy metabolism. Our results suggest that ncRNAs can form DNA/RNA hybrids that influence gene expression, providing preliminary insights into the mechanisms of transcriptional dysregulation in ASD.